Two water environment adaptation models enhance motor behavior and improve the success of the lactate minimum test in swimming rats - Adriano Alves de Lima; Cláudio Alexandre Gobatto; Leonardo Henrique Dalcheco Messias; Pedro Paulo Menezes Scariot; Lucas Dantas Maia Forte; Júlia Odas Santin; Fúlvia de Barros Manchado-Gobatto (Universidade Estadual Paulista (UNESP), 2017)
Abstract AIMS This study was designed to investigate the effects of 14 water environment adaptation days on motor behavior and physiological condition of swimming rats. METHODS Sixty male Wistar rats were divided into four groups-baseline (Bl) and control (Co) groups-which did not perform the water environment adaptation; and sub (SubAnT) and (SupraAnT) anaerobic threshold groups, which performed 14 water environment adaptation days with sub or supra anaerobic threshold progressive loads (from the tenth day), respectively. The climbing-swimming prevalence (i.e. motor behavior) was analyzed during the water environment adaptation days. Lactate minimum test (LMT) parameters and muscular/hepatic glycogen content in addition to serum creatine kinase were also measured. RESULTS Animals from SubAnT and SupraAnT groups presented a lower climbing-swimming pattern throughout the extent of the experiment (p=0.000), especially after the 5th session. These results were achieved without an improvement in the LMT results or glycogen/creatine kinase. In addition, improvements of 26.6% and 25% for the LMT success rate (i.e. LMT reliability) were obtained only for SubAnT and SupraAnT animals. CONCLUSION Overall, we demonstrated that a water environment adaptation period is necessary for lowering the climbing-swimming pattern without physiological improvement.